DEVELOPMENT OF MODULAR EDUCATIONAL PROGRAMMES BASED ON THE FORMATION COMPETENCIES - Zhanguzhinova, Meruyert; Khalykov, Kabyl; Karzhaubaeva, Sangul; Zhanbyrshiev, Orynbasar; Maemirov, Askhat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Development of modular educational programmes based on the formation of trainees’ competencies solves the problem of ensuring a unified approach for the construction of educational programmes of specialties. The implementation of requirements of the Bologna process to ensure the quality of higher education in accordance with the Dublin descriptors implements the novelty of the research in the framework of the modular technology of education in Kazakhstan. The aim of the study is to reveal the process of development of modular educational programmes through the organization of pedagogical process of Formation of Professional competence of trainees. The primary methods used are theoretical generalization, justification and systematization. The study design includes discussions of authors from different countries, definitions of main meanings, schemes, figures, tables. The key results of study is to reveal the Structure, Model, Scheme and stages of the organization of pedagogical process of Formation of Professional competence. Specific asked questions for research in general prospects of implementation of modular educational programmes are formulated in the conclusion.